Handbook of Fuel Cells 2010
DOI: 10.1002/9780470974001.f312108
|View full text |Cite
|
Sign up to set email alerts
|

Life‐cycle analysis of fuel cell system components

Abstract: Higher, if charge sustaining hybrid electric vehicle is assumed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 11 publications
0
13
0
1
Order By: Relevance
“…Available literature and preliminary results indicated that the production of the ammonia fuel would be an important contributor to the environmental impact potential of the Alkammonia system [55,56]. As a consequence, this study also investigates different ammonia production pathways.…”
Section: Ammonia Productionmentioning
confidence: 99%
“…Available literature and preliminary results indicated that the production of the ammonia fuel would be an important contributor to the environmental impact potential of the Alkammonia system [55,56]. As a consequence, this study also investigates different ammonia production pathways.…”
Section: Ammonia Productionmentioning
confidence: 99%
“…6 mg nitrogen oxide and 2 . 7 mg of carbon monoxide per kWh fuel input) with emissions of sulfur dioxide, methane other volatile organic compounds (VOCs), and particulates usually below the detection threshold of measurements (Appleby, 1996;Pehnt, 2003;Rooijen, 2006). Emissions from domestic-scale systems should be similar to these larger units, so long as steam reforming is used.…”
Section: Emissions Emissions Of Local Air Pollutants Frommentioning
confidence: 99%
“…1921 The global decrease in the Pt reserve requires extraction and recovery of this metal (employing harsh acid-digestion techniques) at the end of the lifecycle of the fuel cells. 22 MWNT-TiO 2 NHs that are incorporated into the fuel cell design to support Pt catalysts in fuel cell industry thus have a high likelihood of release during the end of life recovery process.…”
Section: Introductionmentioning
confidence: 99%